Pengaruh Persepsi Pasien tentang Tarif Jasa Pelayanan dan Fasilitas terhadap Keputusan Pasien Memilih Operasi Sectio Caesaria dengan Metode ERACS - Evi Masuni; Erliany Syaodih; Mira Veranita (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The adoption of Enhanced Recovery After Caesarean Surgery (ERACS) has increased due to its clinical advantages; however, patients’ willingness to choose this method remains limited, particularly in relation to economic considerations and hospital service conditions. This study aimed to examine the influence of patients’ perceptions of service fees and hospital facilities on their decision to choose cesarean section using the ERACS method at RSU Prima Medika Tulungagung. A quantitative analytic approach with a cross-sectional design was employed. Data were collected from 43 ERACS patients using structured questionnaires and analyzed through multiple linear regression, supported by t-tests and F-tests at a 5% significance level. The findings revealed that patients’ perceptions of service fees had a positive and statistically significant effect on the decision to select ERACS (β = 0.479; p = 0.002). In contrast, perceptions of hospital facilities did not show a significant effect (β = -0.162; p = 0.341). Simultaneously, service fees and facilities significantly influenced patient decision-making (F = 8.167; p = 0.001), with an adjusted R² value of 0.254. These results indicate that perceived service fees are the dominant factor in patients’ decisions to choose ERACS, while hospital facilities function as a supporting element. Improving cost transparency and strengthening patient education may enhance informed decision-making regarding ERACS services.